2013
DOI: 10.3389/fpubh.2013.00019
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 Antitrypsin Reduces Severity of Pseudomonas Pneumonia in Mice and Inhibits Epithelial Barrier Disruption and Pseudomonas Invasion of Respiratory Epithelial Cells

Abstract: Nosocomial pneumonia (NP) is the third most common hospital-acquired infection and the leading cause of death due to hospital-acquired infection in the US. During pneumonia and non-pneumonia severe illness, respiratory tract secretions become enriched with the serine protease neutrophil elastase (NE). Several NE activities promote onset and severity of NP. NE in the airways causes proteolytic tissue damage, augments inflammation, may promote invasion of respiratory epithelium by bacteria, and disrupts respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 75 publications
(101 reference statements)
2
32
0
Order By: Relevance
“…In the transgenic a1-AT þ/þ mice strain expressing this protein, mortality due to pneumonia caused by Pseudomonas aeruginosa (PA) was reduced by 90% compared with that in nontransgenic mice. 21 Infected mice had reduced lung tissue inflammation and damage, as well as decreased bacterial load. Similarly, EPI-hNE4 (depelestat; Debiopharm S.…”
Section: Animal Models Of Ne Inhibitorsmentioning
confidence: 96%
“…In the transgenic a1-AT þ/þ mice strain expressing this protein, mortality due to pneumonia caused by Pseudomonas aeruginosa (PA) was reduced by 90% compared with that in nontransgenic mice. 21 Infected mice had reduced lung tissue inflammation and damage, as well as decreased bacterial load. Similarly, EPI-hNE4 (depelestat; Debiopharm S.…”
Section: Animal Models Of Ne Inhibitorsmentioning
confidence: 96%
“…Neutrophils release large amounts of elastase following activation, which is normally neutralized by alpha 1 anti-trypsin (AAT). AAT has been shown to significantly reduce airway disease in mice infected with P. aeruginosa pneumonia [101]. Human recombinant AAT (rAAT) is currently under investigation in patients with CF [102].…”
Section: Role Of Immunity In Cf Disease Pathogenesismentioning
confidence: 99%
“…Mice transgenic for human AAT (AAT-tg), which is driven by the surfactin C promoter for selective expression in type-2 lung epithelium,16 have low circulating levels of human AAT but are nevertheless protected in models of multiple sclerosis23 and Pseudomonas pneumonia 24. Here we demonstrated that human AAT-tg mice were also protected against joint inflammation induced by local MSU/C16.0 injection.…”
Section: Resultsmentioning
confidence: 78%